2015
DOI: 10.1039/c5ra00401b
|View full text |Cite
|
Sign up to set email alerts
|

A continuous method to prepare poorly crystalline silver-doped calcium phosphate ceramics with antibacterial properties

Abstract: Silver-doped calcium phosphate ceramics were prepared in discontinuous and continuous processes with different amounts of incorporated silver (up to 1.8 wt% silver).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…This alkaline calcium phosphate has two crystallographic forms β- and α-TCP, and both minerals have been used to prepare DCPD cements [ 1 ]. On the other hand, authors [ 18 ] reported silver-doped calcium phosphate with the Ag + ions incorporated into calcium phosphate lattice and that its heating at 1300 °C led to TCP with almost no silver content. This means that at such a high temperature it is not possible to obtain solid dispersed active phase containing Ag + for the DCPD cement systems.…”
Section: Resultsmentioning
confidence: 99%
“…This alkaline calcium phosphate has two crystallographic forms β- and α-TCP, and both minerals have been used to prepare DCPD cements [ 1 ]. On the other hand, authors [ 18 ] reported silver-doped calcium phosphate with the Ag + ions incorporated into calcium phosphate lattice and that its heating at 1300 °C led to TCP with almost no silver content. This means that at such a high temperature it is not possible to obtain solid dispersed active phase containing Ag + for the DCPD cement systems.…”
Section: Resultsmentioning
confidence: 99%
“…[113][114][115][116] However, the incorporation of silver must be strictly controlled during the synthesis, since this inuences the silver release kinetics. Range et al 117 compared two kinds of silver-containing biomaterials, namely, stoichiometric silver phosphate and silver-doped calcium phosphate; antimicrobial studies showed that both had a high bactericidal effect. However, due to a high release rate of silver ions in stoichiometric silver phosphate, it leads to a cytotoxic effect on eukaryotic cells as well, making the silver phosphate unsuitable as a silver-containing ceramic material.…”
Section: Dopantsmentioning
confidence: 99%
“…It is widely known that the antibacterial activity of Ca-based biomaterial is mainly based on several factors, including high pH and calcium ion release dissolved from the materials. 43,44 In this study, during the hydration process, the C 2 Si-xZn and C 2 Si-xCu reacted with water to show a fast increase in CH, which released hydroxyl ions leading to the creation of an alkalic environment for bacteria to die. Saghiri et al reported that by nano-sizing (40-100 nm) calcium silicate-based particles, the increased exposed surface area of the material would effectively elevate the pH and increase the calcium ion release in solution.…”
Section: Antibacterial Activity In Vitromentioning
confidence: 89%